Intellectual Capital, Innovation, and Performance of Indonesian MSMEs During the Covid-19 Pandemic - Roza Mulyadi; B. Basuki (Australasian Accounting, Business and Finance Journal, 2024)
This research is important in examining the determinants of performance of MSMEs in Indonesia during the COVID-19 pandemic from a non-financial perspective. This influence is meaningful for companies that non-financial intangible assets can affect the performance of MSMEs. This study looks at whether Intellectual Capital which consists of Human Capital, Structural Capital, Customer Capital, and Innovation, affects the performance of MSMEs during the COVID-19 pandemic. This study uses multiple regression analysis. The research sample is 308 MSMEs registered in Indonesia's Gofood and Grabfood applications. The results of hypothesis testing state that H1, H2, H3, and H4 are accepted. It shows that the variables of human capital, structural capital, customer capital, and innovation positively affect the performance of MSMEs. The performance of MSMEs in Indonesia during the COVID-19 pandemic from a non-financial perspective was influenced by several factors, namely human capital, structural capital, customer capital, and innovation.
Keywords: Customer Capital; Human Capital; Innovation; Performance; Structural Capital